Enforcement of the Law Against Negligent Traffic Violators Resulting in Fatalities: A Case Study of Decision Number 34/Pid.B/2021/PN.Mgt - Istiawan, Indah Ramadhani (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2024)
Toll roads are constructed to connect distant locations, aiming to reduce travel time and facilitate mobility and transportation. However, the extended travel distances often result in driver fatigue and drowsiness, increasing the risk of traffic accidents. Law enforcement in cases of traffic accidents resulting in fatalities is an effort to uphold legal norms as guidelines for behavior in traffic and to maintain legal order in society. This study examines two main issues: (1) how law enforcement is carried out against negligent drivers responsible for fatalities and (2) the legal considerations of judges in adjudicating cases of fatal traffic negligence. This study employs a normative juridical method with a statutory approach and qualitative normative analysis using inductive reasoning. Law enforcement against drivers causing fatal accidents involves investigations to collect evidence clarifying the crime and identifying suspects. In this case, the suspect was charged with violating Article 310 paragraph (4) and Article 312 of the Traffic and Road Transportation Law (LLAJ Law), carrying a maximum penalty of six years’ imprisonment and/or a fine of IDR 12,000,000, along with an additional penalty of up to three years’ imprisonment for further violations. The findings reveal that the suspect was legally and convincingly proven guilty of negligence in driving, which resulted in an accident causing four fatalities. In their legal considerations, the judges emphasized the ultimum remedium principle as the basis for sentencing, while also taking into account aggravating and mitigating factors in issuing a verdict of three years and two months’ imprisonment. These findings highlight the challenges in enforcing traffic laws in Indonesia, including the low level of legal awareness among drivers and the lack of an effective preventive system to reduce accidents caused by negligence.